Literature Reviews In Social Work - Kiteley, Robin; Stogdon, Chris (Thousand Oaks, California SAGE, 2014)
This book will provide you with a clear and accessible guide to the process of conducting a literature review, giving you the skills, confidence and knowledge required to produce your own successful review.
Keywords: Social sciences; Social sciences